Rancang Bangun Sistem Informasi Inventory CV. Okta Berbasis Web Menggunakan Model Prototype - Audi, Salman; Dwanoko, Yoyok Seby; Setiyaningsih, Wiji (Department of System Information, 2026)
A web-based inventory information system was designed and developed for CV. Okta, a packaging production company that experienced difficulties in managing its inventory due to inefficient and unstructured recording methods. Inventory data had been written on paper and later transferred to Excel, resulting in delays, input errors, and difficulty tracking stock levels. To solve these problems, the system was built using the prototype method, allowing users to provide feedback during each development stage. The system was developed with PHP and utilized Laragon as its database environment. The design included use case, activity, sequence, and class diagrams. System testing was conducted using the Blackbox method and User Acceptance Testing (UAT) to evaluate whether the system met user needs. The UAT results showed an average score of 82.73%, indicating the system worked effectively. This system improves the speed, accuracy, and accessibility of inventory management for administrators, warehouse operators, and company leaders at CV. Okta